Dozór kuratora sądowego nad sprawcami wymagającymi stosowania szczególnych środków leczniczych lub terapeutycznych. Tymczasowy element zmian w prawie czy może ich nieunikniona perspektywa? - Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The essence of this paper is to present the most important issues related to the execution of professional duties by adult probation officers in Poland. In criminal proceedings they were given a number of tasks within a custodial sentence and probation measures. Since 2009 they have also played an important part in the system of electronic surveillance. They are also increasingly present in the process of punishment execution and isolation measures.
Keywords: kurator sądowy; postępowanie egzekucyjne; warunki zawieszenia; kara ograniczenia wolności; godzina policyjna monitorowana elektronicznie